Constitucion of subjectivities in young people from the educational practices of sex education (2020)
The present article sets forth an approach in terms of the constitution of subjectivities. From teaching practices, with reference to sex education in a group of young students who are attending to the Institución Educativa Zaragoza from the municipality of Cartago. The research was developed from a based on critical analysis. We used a focal group that originated three categories that rotate around the deployment of the sexuality, discourses about the sexuality and the subjectivity. By means of these were evident the relations of knowledge-power that interweave in the dynamic of educational practices. Realizes the way how public policies based on biopowe, have been articulating through the device of sexuality.